FAKTOR RISIKO TUBERKULOSIS PARU KASUS KAMBUH DI RSUD DR. PIRNGADI KOTA MEDAN - DEWI AGUSTIN HAKIM HARAHAP; ANNISA .; SRI REZEKI ARBANINGSIH; HUMAIRAH MEDINA LIZA LUBIS (JURNAL ILMIAH SIMANTEK, 2021)
Pulmonary tuberculosis is an infectious infectious disease caused by the bacterium Mycobacterium tuberculosis. Pulmonarytuberculosis is one of the ten diseases that cause the largest mortality rate in the world. In addition to the increasing numberof new tuberculosis cases, the high number of cases is also due to pulmonary tuberculosis cases which tend to recur. Todetermine the risk factors for relapse in pulmonary tuberculosis in RSUD Dr. Pirngadi Medan City. This type of research isdescriptive observational with the research design used is a cross sectional study. The research method used is logisticregression. Medical record data as a research instrument that has been validated is 94 research samples. Age ofrespondents in relapse cases where the most age was >45 years, based on gender the most were men as many as 37people (78.7%), based on smoking habits, based on a history of disease Most of them did not have a history of diabetesmellitus, based on adherence to taking medication, where the most patients were non-adherent to taking medication, basedon work where. Data analysis obtained p<0.05 on factors of age, gender, diabetes mellitus, smoking habits, medicationadherence and work status with a value of p=0.113 (p≥0.05) Factors that have an influence on the incidence of relapsepulmonary tuberculosis are diabetes mellitus, smoking habits and adherence to medication.